The Effects of Allium Cepa Extract on Tracheal Responsiveness, Lung Inflammatory Cells and Phospholipase A2 Level in Asthmatic Rats - Vahideh Ghorani; Narges Marefati; Farzaneh Shakeri; Ramin Rezaee; Marzie Boskabady; Mohammad Hossein Boskabady (Iranian Journal of Allergy, Asthma and Immunology, 2018)
Antioxidant, antimicrobial, anti-hyperglycaemic, anti-diabetic and anti-inflammatory effects of Allium cepa (A. cepa) have been previously shown. In this study, the effects of A. cepa aqueous-alcoholic extract on tracheal responsiveness, lung inflammatory cells and phospholipase A2 (PLA2) level in bronchoalveolar fluid (BALF) of asthmatic rats were examined. Wistar rats were randomly divided into control group (C), asthmatic group (A), asthmatic group (A) treated with A. cepa extract (AC, 0.175, 0.35, and 0.7 mg/mL) and dexamethasone (D, 1.25 μg/mL). The extract of A. cepa and dexamethasone were added to animal's drinking water during sensitization period. Tracheal responsiveness to methacholine and ovalbumin, lung inflammatory cells and PLA2 level in BALF were assessed. Tracheal responsiveness to methacholine and ovalbumin, PLA2 level, total and most differential WBC count were increased but lymphocytes was decreased in asthmatic animals compared to group C (p<0.05 to p < 0.001). Treatment of sensitized rats with dexamethasone and all concentrations of A. cepa lead to a significant decrease in total WBC and PLA2 level compared to asthmatic group (p<0.001). The two higher concentrations of A. cepa also significantly decreased tracheal responsiveness, neutrophil and eosinophil counts but led to a significant increase in lymphocytes count compared to asthmatic group (p<0.05 to p<0.001). Treatment of sensitized group with the highest concentration of A. cepa also significantly reduced monocyte count compared to asthmatic group (p< 0.001). Anti-inﬂammatory and preventive effects of A. cepa on tracheal responsiveness and lung inflammation in asthmatic animals may suggest its potential therapeutic effect on airway diseases such as asthma.